PREPARATION OF POROUS CARBONS FROM HALLOYSITE-SUCROSE MIXTURES - Wang A.; Kang F.; Huang Zh.; Guo Zh. (My University, 2006)
Porous carbons rich in mesopores and with large pore volumes have been prepared by polymerization and carbonization of a carbon precursor, sucrose, within a matrix of the natural clay, halloysite. The carbon precursor was impregnated into the pores of halloysite and mostly deposited on the external surface of the halloysite rods during impregnation. The inorganic matrix was removed by washing the carbon-mineral composite with HF and HCl. The resultant carbons were characterized by nitrogen adsorption analysis and were found to possess a large specific surface area, a large total pore volume and significant mesoporosity, without an activation process being involved. The pore volume and mesoporosity were up to 1.86 cm3/g and 78%, respectively, even at low carbonization temperatures (500°C). The size of the mesopores of the resultant carbons is mainly between 3 and 30 nm and the dominant pore size is ~3.7 nm. The carbonization temperature has significant effects on the pore-size distribution and structure of the resultant carbons and carbon-mineral composites, respectively. This process is relatively simple and expected to cost less than the high-temperature carbonization process in the preparation of mesoporous carbons with total pore volume and large specific surface areas.
Keywords: ADSORPTION; ELECTRON MICROSCOPY; NATURAL CLAY; PORE VOLUME; PORE-SIZE DISTRIBUTION; POROUS CARBON